Synchronized multiartifact reduction with tomographic reconstruction (SMART‐RECON): A statistical model based iterative image reconstruction method to eliminate limited‐view artifacts and to mitigate the temporal‐average artifacts in time‐resolved CT - Chen, Guang‐Hong; Li, Yinsheng (Medical physics (Lancaster), 2015)
Purpose: In x‐ray computed tomography (CT), a violation of the Tuy data sufficiency condition leads to limited‐view artifacts. In some applications, it is desirable to use data corresponding to a narrow temporal window to reconstruct images with reduced temporal‐average artifacts. However, the need to reduce temporal‐average artifacts in practice may result in a violation of the Tuy condition and thus undesirable limited‐view artifacts. In this paper, the authors present a new iterative reconstruction method, synchronized multiartifact reduction with tomographic reconstruction (SMART‐RECON), to eliminate limited‐view artifacts using data acquired within an ultranarrow temporal window that severely violates the Tuy condition. Methods: In time‐resolved contrast enhanced CT acquisitions, image contrast dynamically changes during data acquisition. Each image reconstructed from data acquired in a given temporal window represents one time frame and can be denoted as an image vector. Conventionally, each individual time frame is reconstructed independently. In this paper, all image frames are grouped into a spatial–temporal image matrix and are reconstructed together. Rather than the spatial and/or temporal smoothing regularizers commonly used in iterative image reconstruction, the nuclear norm of the spatial–temporal image matrix is used in SMART‐RECON to regularize the reconstruction of all image time frames. This regularizer exploits the low‐dimensional structure of the spatial–temporal image matrix to mitigate limited‐view artifacts when an ultranarrow temporal window is desired in some applications to reduce temporal‐average artifacts. Both numerical simulations in two dimensional image slices with known ground truth and in vivo human subject data acquired in a contrast enhanced cone beam CT exam have been used to validate the proposed SMART‐RECON algorithm and to demonstrate the initial performance of the algorithm. Reconstruction errors and temporal fidelity of the reconstructed images were quantified using the relative root mean square error (rRMSE) and the universal quality index (UQI) in numerical simulations. The performance of the SMART‐RECON algorithm was compared with that of the prior image constrained compressed sensing (PICCS) reconstruction quantitatively in simulations and qualitatively in human subject exam. Results: In numerical simulations, the 240∘ short scan angular span was divided into four consecutive 60∘ angular subsectors. SMART‐RECON enables four high temporal fidelity images without limited‐view artifacts. The average rRMSE is 16% and UQIs are 0.96 and 0.95 for the two local regions of interest, respectively. In contrast, the corresponding average rRMSE and UQIs are 25%, 0.78, and 0.81, respectively, for the PICCS reconstruction. Note that only one filtered backprojection image can be reconstructed from the same data set with an average rRMSE and UQIs are 45%, 0.71, and 0.79, respectively, to benchmark reconstruction accuracies. For in vivo contrast enhanced cone beam CT data acquired from a short scan angular span of 200∘, three 66∘ angular subsectors were used in SMART‐RECON. The results demonstrated clear contrast difference in three SMART‐RECON reconstructed image volumes without limited‐view artifacts. In contrast, for the same angular sectors, PICCS cannot reconstruct images without limited‐view artifacts and with clear contrast difference in three reconstructed image volumes. Conclusions: In time‐resolved CT, the proposed SMART‐RECON method provides a new method to eliminate limited‐view artifacts using data acquired in an ultranarrow temporal window, which corresponds to approximately 60∘ angular subsectors.